Large transition state stabilization from a weak hydrogen bond. Issue 28 (10th July 2020) - Vik, Erik C.; Li, Ping; Maier, Josef M.; Madukwe, Daniel O.; Rassolov, Vitaly A.; Pellechia, Perry J.; Masson, Eric; Shimizu, Ken D.
Abstract : A series of molecular rotors was designed to study and measure the rate accelerating effects of an intramolecular hydrogen bond. Abstract : A series of molecular rotors was designed to study and measure the rate accelerating effects of an intramolecular hydrogen bond. The rotors form a weak neutral O–H⋯OC hydrogen bond in the planar transition state (TS) of the bond rotation process. The rotational barrier of the hydrogen bonding rotors was dramatically lower (9.9 kcal mol −1 ) than control rotors which could not form hydrogen bonds. The magnitude of the stabilization was significantly larger than predicted based on the independently measured strength of a similar O–H⋯OC hydrogen bond (1.5 kcal mol −1 ). The origins of the large transition state stabilization were studied via experimental substituent effect and computational perturbation analyses. Energy decomposition analysis of the hydrogen bonding interaction revealed a significant reduction in the repulsive component of the hydrogen bonding interaction. The rigid framework of the molecular rotors positions and preorganizes the interacting groups in the transition state. This study demonstrates that with proper design a single hydrogen bond can lead to a TS stabilization that is greater than the intrinsic interaction energy, which has applications in catalyst design and in the study of enzyme mechanisms.